An Energy Harvester for Low‐Frequency Electrical Signals. Issue 6 (5th June 2020) - Wang, Xin; Wilson, Peter R.; Leite, Ricardo B.; Chen, Guiyou; Freitas, Helena; Asadi, Kamal; Smits, Edsger C. P.; Katsouras, Ilias; Rocha, Paulo R. F.
Abstract : A technology to harvest energy from low frequency sources is designed, eliminating the need for up‐conversion techniques. This is accomplished by modeling and tuning the resonant frequency of an energy harvesting system, which comprises a step‐up transformer and a boost converter on a miniaturized printed circuit board prototype. More details can be found in article number 2000114 by Paulo R. F. Rocha and co‐workers.